Discovery of novel 2,3,4,5-tetrahydrospiro[benzo[c]azepine-1,1’-cyclohexan]-5-ol derivatives as PARP-1 inhibitors - Ling Yu; Jian-hui Li; Ju Zhu; You-de Wang; Zhi-wei Yan; Li-ying Zhang; Shuai Li (BMC Chemistry, 2023)
Abstract As an essential marker of cancer treatment, PARP-1 inhibitors could effectively kill tumor cells through a mechanism known as synthetic lethality and are used to treat a variety of cancers. In order to explore novel PARP-1 inhibitors, a series of 22 novel erythrina derivatives were reported and preliminarily explored their mechanism of action. The antitumor activities against four human cancer cell lines including A549, OVCAR-3, HCT-116, and MCF-7 were evaluated, and the preliminary SARs were summarized. Among them, compound 11b exhibited better anti-proliferative effects against A549 cells (IC50 = 1.95 µM). The SI results showed that compound 11b had low toxicity. Moreover, compound 11b displayed excellent PARP-1 inhibitory activities with IC50 values of 19.24 nM. In addition, molecular docking studies provided the rational binding modes of compound 11b in complexes with PARP-1. The flow cytometry assays revealed that compound 11b could induce apoptosis of A549 cells (P < 0.001). Simultaneously, compound 11b could effectively reduce the formation of PAR (P < 0.001). The ADMET prediction results indicated compound 11b had similar properties to rucaparib. Collectively, compound 11b has potential research value for further investigation.